2018
DOI: 10.1039/c8nj01946k
|View full text |Cite
|
Sign up to set email alerts
|

(Fe)MIL-100-Met@alginate: a hybrid polymer–MOF for enhancement of metformin's bioavailability and pH-controlled release

Abstract: Metformin hydrochloride (Met) was combined with iron(iii) chloride and trimesic acid (1,3,5-benzene tricarboxylic acid, BTC) as an organic linker in a short and simple method, providing a MOF in which the drug is a part of the constituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Finally, as the degradation of MIL-101-NH2(Fe) took place, the amount of polymer adsorbed on the nanoMOFs remained constant, suggesting that it bound to newly formed sites during the degradation of the MOF structure ( Figure 4B, step 6). Azizi Vahed et al reported the preparation of a novel MOF: MIL-100-metformin(Fe), an antihyperglycemic agent used for the treatment of type II diabetes that also presents anti-cancer properties [63]. In the MOF structure, the metformin molecules are believed to coordinate iron ions, but without bridging two different ions.…”
Section: Non-covalent Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as the degradation of MIL-101-NH2(Fe) took place, the amount of polymer adsorbed on the nanoMOFs remained constant, suggesting that it bound to newly formed sites during the degradation of the MOF structure ( Figure 4B, step 6). Azizi Vahed et al reported the preparation of a novel MOF: MIL-100-metformin(Fe), an antihyperglycemic agent used for the treatment of type II diabetes that also presents anti-cancer properties [63]. In the MOF structure, the metformin molecules are believed to coordinate iron ions, but without bridging two different ions.…”
Section: Non-covalent Attachmentmentioning
confidence: 99%
“…The coated nanoparticles were characterized by Fouriertransform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and x-ray diffraction (XRD) (indicating the MOF crystallinity is retained). The MIL-100-Metformin(Fe) nanoparticles were Azizi Vahed et al reported the preparation of a novel MOF: MIL-100-metformin(Fe), an antihyperglycemic agent used for the treatment of type II diabetes that also presents anti-cancer properties [63]. In the MOF structure, the metformin molecules are believed to coordinate iron ions, but without bridging two different ions.…”
Section: Non-covalent Attachmentmentioning
confidence: 99%
“…Upon exposure to aqueous sodium citrate solution, the alginate coating was degraded, and the ethylene was gradually released from the MOF pore space. Similarly, the pH-controlled drug release of metformin was achieved by Naimi-Jamal and coworkers using alginate-coated (Fe)­MIL-100 . In an alternate method by Huang, Huo, Xu, and coworkers, doxorubicin drug molecules were encapsulated in selenium-containing polymer micelles, which were then trapped within ZIF-8 frameworks .…”
Section: Functional Applications Of Polymer/mof/moc Hybrid Materialsmentioning
confidence: 99%
“…Nanosized MIL-100(Fe) is widely reported to be unstable [ 27 , 28 ]. Surface modification strategies were developed to prevent MOFs from aggregation, including coating with lipids [ 28 , 29 , 30 ], polymers [ 31 , 32 , 33 ], and cyclodextrins (CDs) [ 27 , 34 , 35 ]. A particular focus was on nanoMOFs’ surface engineering with CD derivatives [ 27 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%